Analysis of Human Rights Protection and Enforcement Based on Local Wisdom in Indonesia - Yasmiati, Ni Luh Wayan; Yudiawan, I Dewa Gede Herman (JOM, 2024)
This article examines the role of local wisdom in the protection and enforcement of Human Rights (HR) in Indonesia, focusing on how local customs, cultural values, and customary laws contribute to a more holistic approach to HR. The study aims to explore how local wisdom can enhance HR protection and address challenges in aligning traditional values with universal HR principles. Employing a qualitative research design, this study utilizes a case study approach across multiple regions in Indonesia, analyzing specific instances where local wisdom has been integrated into HR practices. The findings reveal that local wisdom, including community-based conflict resolution mechanisms, traditional justice systems, and cultural norms, significantly contributes to HR enforcement by ensuring the inclusion of indigenous perspectives in legal frameworks. However, challenges arise in harmonizing local practices with national and international HR standards, particularly when local values conflict with universal rights. The research highlights that a participatory approach, which incorporates both local and global HR principles, is essential in crafting an inclusive legal system. The theoretical implication of this study suggests that integrating local wisdom into HR frameworks could lead to a more contextualized and culturally sensitive approach to HR, thereby fostering greater social cohesion and respect for diversity while safeguarding fundamental human rights. This integration requires cooperation from multiple stakeholders to maintain a balance between honoring cultural traditions and upholding universal HR norms.